THE EFFECT OF BRAND TRUST ON BRAND LOYALTY WITH BRAND LOVE AS A MEDIATOR - Putu Adi Surya Prayoga; Ni Wayan Ekawati (CV. Adiba Aisha Amira, 2025)
The fashion industry in Indonesia, particularly in Bali, has grown rapidly in recent years, driven by trends influenced by globalization. This development has led to the emergence of various local Balinese fashion brands competing in the market. One of these brands is Karung Jantan. This study aims to examine the mediating role of brand love in the influence of brand trust on brand loyalty among Karung Jantan consumers in Denpasar. The research is grounded in the Theory of Planned Behavior, which posits that individuals’ intentions drive their behavior, influenced by initial motivational factors. The study was conducted in Denpasar using purposive sampling. A total of 100 respondents were surveyed using offline questionnaires. Data were analyzed using path analysis with SPSS 24.0. The results support all hypotheses: brand trust has a positive and significant effect on brand loyalty; brand trust positively and significantly affects brand love; brand love positively and significantly influences brand loyalty; and brand love successfully mediates the relationship between brand trust and brand loyalty.